From IT to I-It: Digitalization, datafication, automation, and the teacher-student relationship - Mertala, Pekka (Journal of Childhood, Education & Society, 2024)
This conceptual article theorises the tensioned interplay between digitalization, datafication and automation and subjectness in education by asking what intensifying datafication and automation means for teacher–student relationships and how we understand and approach education. Theoretically, the paper draws on Buber’s ideas of the dialogical I–Thou and objectified I–It as the key forms of human relationships. The core argument is that increasing datafication and automation steers the teacher–student relationship towards an objectified I–It relationship instead of the dialogical I–Thou relationship, which Buber (and others such as Biesta, another main influencer of the present paper) saw as the ideal. Literature-informed examples of various forms of educational datafication and automation are provided to support and concretise the arguments.